Health Informatics: The Transformative Power of Innovation - Hansen, David P. (IOS Press, 2014)
Australia has a long history of involvement in the progress of health informatics, and Australian contributors have made an impact on the world health informatics scene in numerous areas, including software development, standardisation, evaluation, policy development and education. The Health Informatics Society of Australia (HISA), has been reporting on these developments for 19 years, and its annual Health Informatics Conference (HIC) constitutes the premier Australian academic platform for a wide range of topics in health informatics. This book presents the proceedings of full scientific papers from this annual conference for the first time in monograph format. The focus of HIC 2011 draws on a fundamental aspect of health informatics: its ability to transform processes and practices within healthcare through innovation. The 24 papers were selected after a rigorous double-blind peer review process from the 39 submitted. The topics included cover a wide range of different sectors in the health system, from primary and acute care to preventative and public health. Many of the papers not only provide solid background and technical substance, but also exhibit practical implementations and demonstrations of their worth. The book offers a comprehensive profile of active research areas in Australian health informatics.